Nilai Signifikansi Budaya Bangunan Lama di Kawasan Alun-Alun Merdeka Kota Malang Berdasarkan Persepsi Masyarakat - widiana, fenny; Santosa, Herry; Ernawati, Jenny (RUAS, 2022)
Historic buildings that still survive for a long time can affect the image of an area. To study this, this research identified people's perceptions of historical buildings in the Merdeka Square area of Malang. This study used multiple rating scales measuring instruments and photos of eight historic buildings around the Merdeka Square, Malang City as stimuli to investigate the similarities and differences in perceptions between three groups of respondents: the general public, professionals in the field of Architecture (lecturers and students majoring in Architecture, and members of the Indonesian Architectural Association), and the Government (Bappeda, Culture and Tourism Department, and Malang City DPUPR). The results of this study indicated that the order of the most influential cultural significance factors in shaping the image of the Merdeka Square area of Malang is the intangible value and the visual quality of the facade of the old building. It was also found that there were differences in assessment between groups of respondents in assessing the visual quality of the building facade in its effect on the image of the area.